(untitled) (Scientific journal of the Fergana State University, 2023)
The article presents an analytical review of intelligent systems in distance education based on an individualized approach. There is shown relevance of the development of multi-agent systems in the creation of innovative adaptive intelligent environments for online learning, based on the use of various approaches and system analysis. Special attention is paid to cognitive agents that have behavioral and emotional functions of interaction with students in the learning system. The importance of individualization of e-and distance education for students with different levels of knowledge and prospects for their development is shown. There are presented main advantages and disadvantages of using an individualized approach in the construction of adaptive intelligent online distance learning systems.